POLA KOMUNIKASI KELUARGA (LAISSEZ FAIRE, PROTEKTIF, PLURALISTIK, DAN KONSENSUAL) IBU PEKERJA LAPAS TERHADAP PENGASUHAN ANAK - Azizah, Meylin (Universitas Muhammadiyah Lampung, 2022)
ABSTRACT The phenomenon occurs now, the mother who worked in formal hours unconsciously ignoring their children. The material which is received by children is not comparable to affection that should be given. Parents can just physically close to their children but not psychologically, so they did not feel the presence of their parents. Woman actualization that has been married is not always accompanied by good family communication pattern to their childcare. Woman who have career but can not do the best caring for their children causing its own problem. The research was done to understand family communication female employee who have hours night time job manifested by individual characteristics, family characteristic, laissez faire communication pattern, protective pattern, pluralistic pattern, and consensual pattern. Social economic support, institution support, social system support, and mass media information through parenting reception-rejection. This research was conducted in Woman Correctional Institution Grade II A Bandar Lampung in April-July 2016. The result showed that mother age, mother educational, father earn, laissez faire pattern and protective pattern, family economic support and social system support significantly affect to affection attitude or parents reception care. Keyword: working woman, family communication pattern, parental reception-rejection